Implementation of Good Governance for Zakat Management (Case Study at Baznas Kudus Regency) - Jadzil Baihaqi; Saida Ulfa (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This study aims to analyze the implementation of good governance in Zakat Management Organisation (Baznas) Kudus. This study uses a qualitative method with an interpretive approach. The type of research is field research. The setting of the research was carried out at the Badan Amil Zakat Nasional (Baznas) of Kudus Regency. Data analysis techniques using data reduction, data presentation, and concluding. The informants of this research are the staff of Baznas Kudus and zakat stakeholders. The results of this study indicate that BAZNAS Kudus has been quite good in implementing the principles of transparency, accountability, responsibility, independence, and fairness. Komite Nasional Kebijakan Governansi (KNKG) in 2022 has issued General Guidelines for the Governance of Indonesian Non-Profit Organizations. The governance principles are transparency, accountability, ethics, and sustainability. For further research, this guide can be used as an analysis tool for the implementation of good governance in nonprofit organizations.